Quantitative proteomics reveals new insights into erythrocyte invasion by Plasmodium falciparum - Kuss, Claudia (2011)
Differential expression of ligands in the human malaria parasite Plasmodium falciparum enables it to recognize different receptors on the erythrocyte surface thereby providing alternative invasion pathways. Switching of invasion from using sialated to non-sialated erythrocyte receptors have been linked to the transcriptional activation of a single parasite ligand. We have used quantitative proteomics to show that in addition to this single known change there are a significant number of changes in the expression of merozoite proteins that are regulated independent of transcription during invasion pathway switching. These results demonstrate a so far unrecognized mechanism by which the malaria parasite is able to adapt to variations in the host cell environment by posttranscriptional regulation.